The Level of Study of the Religious Image of Mavarounnahr in the IX-XII Centuries - Doniyorov, Alisher; Kariev, Adil; Aminov, Hamidulla; Karimov, Nodir (The journal of contemporary issues in business and government, 2021)
This article analyzes the level of study of the religious image of Msvarounnahr in the IX-XII centuries. From the 8th century onwards, the number of such categories and groups as Qadariyya, Jabriya, Jahmiya, Mutaziliyya, and Rafidiyyah, which began to appear in Islam, increased in the late ninth and first half of the tenth centuries. These groups were widespread throughout the Islamic world, especially in Central Asia. Their emergence, meaning, and impact on socio-political processes have been extensively covered in the studies of Wilfred Madelung [22], Melchert Christopher [25], Ahmet Karamustafa [19], Akiner Shirin [2], Muhammad Mansur Ali [27], Aiyub Palmer [31] and other scholars. A general conclusion from their work is that Mavarounnahr, or modernly speaking, Central Asia is described as a region where hadith scholars (Ahl al-hadith), Hanafiism, and Moturidism flourished. These scholars also noted that the areas that embodied some of the features of Sufism (malamatiya, karramiya, etc.) were also closely related to Islamic sects. It is written that the representatives of hadith, Hanafi and Moturidi fought against groups that misrepresented religious issues. There are also a number of studies [49] on the differences between the views of the Ahl al-Hadith and the Hanafi (in some literatures Abu Hanifa is mentioned as a representative of the Ahl al-Ray [8]). According to Khalid Blankinship and Ira Lapidus, in the tenth century, the Samarkand scholar al-Moturidi created the doctrine of moturidia, which combines only the positive aspects of various conflicting directions [6][20]. In other words, Imam al-Moturidi further developed the theory founded by Abu Hanifa, the founder of the Hanafi school, and based the Qur'an and hadiths on groups such as Jahmiyyah, Qaramit, Rafidiyyah, Murjiyyah, and Karramiyyah, which undermined the purity of Islam and misinterpreted religious issues. The work we are analyzing aims to study the research on Hanafi, Ahl al-Hadith and other groups that were widespread in Central Asia, and to determine their main directions.